Influential Factors of Online Shopping Decision - I Putu George Budiananta Merta; N. Trinanasari; I Wayan Bagia (Universitas Pendidikan Ganesha, 2022)
With the technology advances, online shopping has experienced a phenomenal growth. In line with such phenomenon and its relevancy, a considerable number of studies have shown an interest within this area. Although recent researches have particularly addressed the online consumer’s behavior, findings were inconsistent. Thereby, further researches have been called for. The present study aims to investigate the effect of few variables derived from existing literature which are price, trust, promotion, easiness, service quality, and product on online consumers’ buying decision. A survey method was employed to gather data from 84 university’s students. They were recruited using purposive sampling technique in which previous online shopping experiences was required. Data were then analyzed using multiple regression. The results of data analysis showed that the six factors significantly affect consumer’s buying decision. Moreover, this study revealed that the largest contributor of these influences was price. Further discussion and managerial implications are presented.